Review Challenges of Implementing Transformational Leadership in Football: Current and Future - Shamil Mohd Ameen Naji Al-Daghistani, Prof K. Ramanathan Kalimuthu (International Journal of Advanced Science and Technology, 2020)
The transformational leadership has now been applied to a sports context for a decade and was critically discussed in terms of the empirical studies.  The following variables were the most in transformative leadership: intellectual stimulation was the most perceived leadership behavior followed by idealized influence, inspirational motivation, and individual consideration.  To make a difference to applied practice and policy, the transformational leadership construct requires a refined definition and stronger empirical tests allowing for robust causal inference.  The majority of studies used cross-sectional designs and single-source questionnaires to tap what has been a fuzzy construct.  The current theoretical and methodological issues impede understanding of whether transformational leadership matters for sports outcomes.  The purpose of this study was to review the developments that encounter the construction of a research framework for the effect of transformational leadership on the satisfaction of the players.  The article discusses the intermediate level between the independent and the dependent variables which contains the moderator and mediator to expand the domain of the research framework research.  The theoretical foundation of the moderating and mediating was also provided.  The article concludes that the complexity could be more transparently captured by considering moderating and mediating variables.  We highlight avenues for advancing research on transformational leadership in the sport context.  Results from past research have shown that the level of satisfaction when using transformative leadership and the satisfaction measure by players.  The results showed that the satisfaction level was generally average and the degree of exercise of transformational leadership by trainers was average.